Wyatt Earp [videorecording (DVD)] - Kasdan, Lawrence, 1949-; Kasdan, Lawrence, 1949-; Kasdan, Lawrence, 1949-; Costner, Kevin; Costner, Kevin; Quaid, Dennis; Hackman, Gene; Harmon, Mark, 1951-; Williams, JoBeth; Winningham, Mare (Warner Bros. Pictures : Distributed by Warner Home Video, 2004)
Who was Wyatt Earp? Was he a hero? A civilized man who became a killer? A gifted lawman? A man who catechized violence? This romanticized biopic begins at the beginning, with Wyatt born on a farm with a stern but loving father, a kind but realistic mother, and many brothers. He studies law, takes a wife, buys a house, and settles into an unremarkable life. When his wife dies, he goes off the deep end--ending up in prison. Freed by his father, he flees, and begins a new life. This life will take him to Dodge City, where along with brothers Virgil and Morgan he becomes a lawman. He befriends Doc Holiday, and earns a reputation while accumulating a long list of enemies. When tragedy befalls one of the Earp brothers, Wyatt goes on a hunt to avenge his family's honor and in the process thrusts himself permanently into the folklore of the American West.